Emerging role of spectral computed tomography in neurocardiology - Fontana, Lucia (2021)
The complex and reciprocal relationship between the brain and the heart has gained increasing attention under the concept of neurocardiology. Myocardial injury is common in cerebrovascular disease, and cardiovascular complications are the second leading cause of death after stroke. Cardiac computed tomography (CT) is a fast and reliable non-invasive tool for the assessment of cardioembolic sources. Compared to single energy CT, spectral/dual energy cardiac CT improves tissue characterization and also leads to significant reductions in contrast volume. In this review article, we portray the potential clinical applications of spectral CT in neurocardiology, focusing in the enhanced diagnosis of cardioembolic sources and cardiovascular risk assessment of patients with stroke, including improved detection of thrombus, identification of subtle myocardial disease, and pulmonary complications within the same session.